Jonathan Sacks: Universalizing Particularity - Tirosh-Samuelson, Hava (Library of Contemporary Jewish Philosophers Ser., 2013)
This volume features the thought and writings of Jonathan Sacks, one of today's leading Jewish public thinkers. It brings together an intellectual portrait, four of his most original and influential philosophical essays, and an interview with him.